Plantar pressures in male adolescent soccer players and its associations with bone geometry and strength - Lozano-Berges, G.; Matute-Llorente, Á.; Gómez-Bruton, A.; Alfaro-Santafé, V.; González-Agüero, A.; Vicente-Rodriguez, G.; Casajús, J. A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Mechanical loads exerted by soccer-specific actions increase bone remodeling activity. Nevertheless, little is known about the relationship between plantar pressure and bone structure. Therefore, the aim of this study was to compare bone geometry and strength between soccer players who exhibited different maximum values of the average pressures (MP) when performing a combination of soccer-specific tasks. METHODS: Forty male adolescent soccer players (mean age 13.2±0.5 years) and 13 controls (mean age 13.1±0.9 years) participated in this study. Biofoot® system was used to measure MP at the non-dominant foot during a circuit of soccer-specific tasks. Cluster analysis was performed to classify players into groups of similar MP profiles resulting two different groups as follows: 15 players with high MP (SOC-HP; mean MP: 392.7±68.2 kPa) and 25 with low MP (SOC-LP; mean MP: 261.0±49.6 kPa). Total and cortical volumetric bone mineral content (Tt.BMC/Ct.BMC), cross-sectional area (Tt.Ar/Ct.Ar), cortical thickness (Ct.Th), fracture load in X-axis, and polar strength index (SSIp) were measured at 38% of the non-dominant tibia by peripheral quantitative computed tomography. Bone geometry and strength comparisons between SOC-HP and SOC-LP were performed using analyses of covariance controlling by weight and tibia length. RESULTS: Greater Tt.BMC, Ct.BMC and Tt.Ar. were found in SOC-HP compared to CG (Tt.BMC: 3.22vs2.95 g, Ct.BMC: 2.95vs2.68 g, Ct.Ar: 280vs253 mm2; P<0.05). Nevertheless, no significant bone geometry and strength differences were found between soccer groups and between SOC-LP and CG (P>0.05). CONCLUSIONS: Developing high MP when training and playing soccer might be favorable to bone development.